Hukum Adat Sebagai Alternatif Penyelesaian Perkara Pidana Dalam Pendekatan Restorative Justice - Panjaitan, Yakub Biyagi; Dewi Ayu Rahayu (Postgraduate University of Merdeka Malang, 2024)
In the context of criminal law, the reality of the existence of customary criminal law alongside statutory criminal law still appears difficult to accept for application in criminal justice practice. The fundamental principle of legality is often argued as a strong barrier to negating the existence of any criminal law other than statutory criminal law. The research problem raised is whether customary law can be used as an alternative for resolving criminal offenses and how the position of customary law functions as an alternative resolution within the framework of restorative justice in the Indonesian criminal justice system. This research employs normative legal research methods. The study’s findings indicate that several jurisprudences have used customary law as an alternative resolution for criminal offenses, including PN Luwuk No. 27/Pid/1983, which adjudicated a case of extramarital sexual relations, where the judge ruled that the defendant violated the living law in the Banggai region, Central Sulawesi. The decision was upheld by the Palu High Court ruling No. 6/Pid/1984 on April 9, 1984, and later reinforced by the Supreme Court decision No. 666K/Pid/1984 on February 23, 1985. Additionally, the Supreme Court ruling No. 3898K/Pdt/1989, dated November 19, 1992, case No. 854K/Pid/1983 dated October 30, 1984, Mataram District Court Decision No. 051/Pid.Rin/1988 dated March 23, 1988, Supreme Court decision No. 481 K/Pid/1986 dated August 31, 1989 from PN Ende, and the application of customary justice in Papua Province based on Law No. 21 of 2001 in conjunction with Law No. 2 of 2021 concerning Special Autonomy for Papua. The material position of customary criminal law has been applied and incorporated into written regulations, particularly statutory law, as seen in Emergency Law No. 1 of 1951. However, in a formal sense, customary criminal law has not been regulated by a standardized set of procedural rules, and its procedural aspects are not established in Indonesia’s positive law. It is also not formally recognized or regulated in the Indonesian Code of Criminal Procedure (Law No. 8 of 1981). However, a review of several Indonesian jurisprudences reveals that customary law has been applied as an alternative resolution within the framework of restorative justice in the Indonesian criminal justice system. Furthermore, if we examine the customary justice system currently used in Papua Province, as regulated in Law No. 21 of 2001 in conjunction with Law No. 2 of 2021 on Special Autonomy for Papua, as well as the shift in criminal punishment patterns from a retributive justice concept to restorative justice, it becomes evident that this transition is part of the effort to revitalize the position of customary law within the realm of the criminal justice system.